Nasal lysine aspirin challenge in the diagnosis of aspirin ‐ exacerbated respiratory disease: Asthma and Rhinitis. Issue 8 (29th July 2013) - Miller, B.; Mirakian, R.; Gane, S.; Larco, J.; Sannah, A. A.; Darby, Y.; Scadding, G.
Summary: Background: Aspirin‐exacerbated respiratory disease is under‐diagnosed and therefore effective and inexpensive therapy with aspirin desensitization is rarely performed. Methods: We present an audit of 150 patients with difficult to treat nasal polyposis, 132 of whom also had asthma, 131 of whom underwent challenge with the only soluble form of aspirin, lysine aspirin (LAS), to confirm or exclude the diagnosis of aspirin‐exacerbated respiratory disease (AERD). Results: One hundred patients proved positive on nasal challenge, 31 who were negative went onto oral LAS challenge and a further 14 gave positive results, leaving 17 who were negative to a dose equivalent to over 375 mg of aspirin. Nineteen were not challenged because of contraindications. With the exception of one patient who developed facial angioedema and two patients with > 20% drop in FEV1 (following nasal plus oral challenge) no other severe adverse events occurred. No hospitalization was required for these three patients. Nasal inspiratory peak flow monitoring was less sensitive to obstruction caused by aspirin than was acoustic rhinometry – which should be employed when aspirin challenge is an outpatient procedure. Conclusions: Provided patients are carefully chosen and monitored LAS challenge is suitable for ENT day case practice where respiratory physician help with asthma is available and should reduce the under‐diagnosis of this condition.